Syariah Bank Services and Career Opportunities for Non-Muslims in the Perspective of the Quran and the Frame of Religious Moderation - Arifin, Rahman; Adisel, Adisel; Asnaini, Asnaini; Isnaini, Desi; Junaidi, Anwar (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This qualitative research aims to examine the implementation of Bank Mega Syariah KC Jambi services in facilitating non-Muslims in transacting at Bank Mega Syariah KC Jambi and studying the ease of non-Muslims in a career at the bank. The research will also look at the obstacles faced by non-Muslims when making transactions and careers at Bank Mega Syariah KC Jambi and how Islamic law regulates employment agreements for non-Muslims in the Islamic banking sector.The research method used is a qualitative approach with data collection techniques through in-depth interviews with related parties such as non-Muslim customers, employees, and management of Bank Mega Syariah KC Jambi. In addition, documents related to Islamic law and Islamic banking regulations will also be analysed in this research.The results of this research are expected to provide a better understanding of the implementation ofÂ Bank Mega Syariah KC Jambi services in facilitating non-Muslims to transact at the bank. In addition, this research is also expected to provide information about the ease of non-Muslims in a career at Bank Mega Syariah KC Jambi and the obstacles faced when transacting and working at the bank.The results of this study are expected to provide recommendations to Bank Mega Syariah KC Jambi in improving services to non-Muslim customers and creating an inclusive work environment for all employees, including non-Muslims. In addition, this research can also provide a better understanding of how Islamic law regulates employment agreements for non-Muslims in the Islamic banking sector and whether there are certain restrictions or prohibitions related to non-Muslim customer financing service contracts in Islamic banking.